2020
DOI: 10.1016/j.biopsych.2019.11.013
|View full text |Cite|
|
Sign up to set email alerts
|

Cyclin-Dependent Kinase 5–Dependent BAG3 Degradation Modulates Synaptic Protein Turnover

Abstract: BACKGROUND: Synaptic protein dyshomeostasis and functional loss is an early invariant feature of Alzheimer's disease (AD), yet the unifying etiological pathway remains largely unknown. Knowing that cyclin-dependent kinase 5 (CDK5) plays critical roles in synaptic formation and degeneration, its phosphorylation targets were reexamined in search of candidates with direct global impacts on synaptic protein dynamics, and the associated regulatory network was also analyzed. METHODS: Quantitative phosphoproteomics a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 71 publications
2
38
1
Order By: Relevance
“…We noticed that the overexpression of BAG3 also increased the density of dendrites and postsynaptic compartments in the P301S mice. This finding echoes the results from a recent study indicating that exogenous expression of BAG3 in the 5XFAD mouse model increased the expression of synaptic proteins [82].…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…We noticed that the overexpression of BAG3 also increased the density of dendrites and postsynaptic compartments in the P301S mice. This finding echoes the results from a recent study indicating that exogenous expression of BAG3 in the 5XFAD mouse model increased the expression of synaptic proteins [82].…”
Section: Discussionsupporting
confidence: 90%
“…BAG3 is increased with aging [71]. However, recent data suggest that BAG3 expression is decreased in human AD brains compared with the aged control [82]. A previous study in our lab showed that depletion of BAG3 in rat cortical neurons increased the levels of endogenous phosphorylated tau [51].…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations